EFFECT OF YOGA THERAPY ON LUNG FUNCTIONS IN RESPIRATORY DISORDER SUBJECTS - K. Krishna Sharma; Udayakumara K; Thirumaleshwara Prasada H.; Ajithesha N H (European Scientific Journal, ESJ, 2014)
The study entitled “Effect of Yoga therapy on Lung Functions in respiratory disorder subjects” has been done to the workers of Mandovi Motors Pvt. Ltd, Mangalore. 22 volunteer subjects suffering from respiratory problems between the age group 20- 50 years were selected. A 40 days long practical session were conducted from 9th February to 20th March, 2012, with a total of 13 subjects as Experimental group and another 9 subjects as control group. The experimental group was progressively introduced to the selected yogic practices. The session included a series of Āsanas, Prāṇāyāmas, Mudras and Relaxation techniques. The control group was not given any of these practices. The initial and final Lung Function Test readings were taken for both the groups using a Digital Spirometer, namely Helios 401. The results of various tests were analyzed through student ‘t’ test. After Yoga therapy, the experimental group showed a significant improvement in FVC, FEV1,IRV and MVV. But there were no such significant results found in the Control Group.